ADMINISTRATIVE REGULATORY INSTRUMENTS OF SOCIO-ECONOMIC DEVELOPMENT OF SOLAR ENERGY IN UKRAINE - M. Rymkina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper highlights the administrative regulatory instruments of socio-economic development of solar energy in Ukraine. This article considers that the current state of the energy market requires fundamental change. Analysis of international studies and publications indicates the balance between social, economic and environmental aspects that give rise to the development of alternative energy. Scientific originality of this article in a study of the dynamics of solar energy in Ukraine. International studies show that among the proposed renewable energy is the most environmentally friendly solar power. The practical significance of the study is to seek proposals for ensuring effective socio-economic development of enterprises in the industry for the future. For the implementation and development of the national energy strategy based on alternative energy in Ukraine has everything: raw materials, experience, technical and technological developments, training of highly qualified specialists in higher education. An important issue is the comprehensive state support, which will attract additional investment resources. As a result, at the macroeconomic level to mitigate the potential effects of the energy crisis.